A9.01 Characterisation of extracellular histidyl-trnasynthethase in myositis. (24th February 2016) - Fernandes-Cerqueira, C; Sohrabian, A; Albrecht, I; Notarnicola, A; Ossipova, E; Lengqvist, J; Fathi, M; Pruijn, GJ; Grunewald, J; Rönnelid, J; Lundberg, IE; Jakobsson, PJ
Abstract : Background and objectives: Histidyl-transfer RNA synthetase (HisRS) is a major autoantigen in myositis with lung involvement. Simultaneous presence of anti-HisRS and anti-Ro52 antibodies has been demonstrated in patients with myositis. We investigated the presence of HisRS in extracellular compartments such as plasma, sera and bronchoalveolar lavage (BAL). In addition, the occurrence of anti-HisRS antibody isotypes as well as other auto-reactivities was evaluated in BAL and sera from patients with myositis. Materials and methods: HisRS was measured in sera, plasma and BAL from myositis (anti-HisRS antibody positive, anti-Jo1+ and negative, anti-Jo1-), sarcoidosis, rheumatoid arthritis (RA) patients and healthy controls (HC) by dot-blot, western-blot, immunoprecipitation and mass spectrometry. The presence in BAL and sera of anti-Jo1 isotypes and autoantibodies to other reactivities was analysed by ELISA and addressable laser bead immunoassay. Results: HisRS was detected in sera, plasma and BAL fluid of patients with myositis, sarcoidosis and RA and in HC. HisRS systemic levels were elevated in anti-Jo1+ myositis in comparison to anti-Jo1- myositis, sarcoidosis, RA or HC sera. In HC BAL HisRS was detected in significant levels. Experiments demonstrated the presence of a factor in BAL with high binding capacity for HisRS and HisRS complexed with anti-HisRS-N-terminal antibody. Immune complexes (IC) containing HisRS and C1q were not the binding factor. However, several anti-HisRS isotypes (anti-Jo1 IgG, IgM and IgA) as well as anti-Ro52IgG were identified in both BAL and sera. Furthermore, a positive correlation between the presence of anti-Jo1 IgG and anti-Ro52IgG in BAL was identified. Conclusions: HisRS was detected both in blood and BAL fluid. The identification of extracellular HisRS, anti-HisRSisotypes and anti-Ro52 in myositis BAL may provide additional clues for the development of autoimmunity in the lungs.